A Systematic Literature Review of Analytics for Adaptivity Within Educational Video Games - Ninaus, Manuel; Nebel, Steve (Frontiers in Education, 2021)
Research has shown that serious games, digital game-based learning, and educational video games can be powerful learning instruments. However, experimental and meta-research have revealed that several moderators and variables influence the resulting learning outcomes. Advances in the areas of learning and game analytics potentially allow for controlling and improving the underlying learning processes of games by adapting their mechanics to the individual needs of the learner, to properties of the learning material, and/or to environmental factors. However, the field is young and no clear-cut guidelines are yet available. To shed more light on this topic and to identify common ground for further research, we conducted a systematic and pre-registered analysis of the literature. Particular attention was paid to different modes of adaptivity, different adaptive mechanisms in various learning domains and populations, differing theoretical frameworks, research methods, and measured concepts, as well as divergent underlying measures and analytics. Only 10 relevant papers were identified through the systematic literature search, which confirms that the field is still in its very early phases. The studies on which these papers were based, however, show promise in terms of the efficacy of adaptive educational games. Moreover, we identified an increased interest in the field of adaptive educational games and in the use of analytics. Nevertheless, we also identified a clear lack of common theoretical foundations as well as the application of rather heterogenous methods for investigating the effects of adaptivity. Most problematic was the lack of sufficient information (e.g., descriptions of used games, adaptive mechanisms), which often made it difficult to draw clear conclusions. Future studies should therefore focus on strong theory building and adhere to reporting standards across disciplines. Researchers from different disciplines must act in concert to advance the current state of the field in order to maximize its potential.